2015
DOI: 10.1371/journal.pone.0129805
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Cognitive Enhancement in Healthy Individuals: A Compensation for Cognitive Deficits or a Question of Personality?

Abstract: The ongoing bioethical debate on pharmacological cognitive enhancement (PCE) in healthy individuals is often legitimated by the assumption that PCE will widely spread and become desirable for the general public in the near future. This assumption was questioned as PCE is not equally save and effective in everyone. Additionally, it was supposed that the willingness to use PCE is strongly personality-dependent likely preventing a broad PCE epidemic. Thus, we investigated whether the cognitive performance and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 35 publications
(69 reference statements)
4
38
0
Order By: Relevance
“…Social support, which was assumed to be another external resource to achieve valued goals, to deal with problems, or increase well‐being, had no main effect on self‐reported CE‐drug use. Prior studies seem inconclusive with respect to the relation of substance use and support (Maier et al, ; Peck et al, ; Schröder et al, ; Wiegel et al, ), as well as with regard to stress‐buffering effects of support (Peirce et al, ; Steptoe et al, ; Wiegel et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Social support, which was assumed to be another external resource to achieve valued goals, to deal with problems, or increase well‐being, had no main effect on self‐reported CE‐drug use. Prior studies seem inconclusive with respect to the relation of substance use and support (Maier et al, ; Peck et al, ; Schröder et al, ; Wiegel et al, ), as well as with regard to stress‐buffering effects of support (Peirce et al, ; Steptoe et al, ; Wiegel et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It is unlikely that everyone will benefit equally from CE. A recent study suggested that regular users of substances for CE present a personality profile that might explain substance use and efficacy [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…25,41 One study reported that people with subclinical traits related to attention deficit hyperactivity disorder (ADHD), impulsivity, and novelty seeking were more prone to using cognitive enhancers. 62 However, it is possible that people self-medicate or at least try to self-medicate for undiagnosed ADHD traits or subjective cognitive deficits, 63 as well as for motivational problems 45,64 and diminished inhibitory control resulting in increased impulsivity. 65 Another study reported similar subjective attention impairments/ADHD symptoms, but also increased omission errors in an attention test in users of (unprescribed) stimulants.…”
Section: Studies On Pharmacological Cognitive Enhancers In Healthy Vomentioning
confidence: 99%